1986
DOI: 10.1139/v86-372
|View full text |Cite
|
Sign up to set email alerts
|

Squaraine chemistry. Synthesis of bis(4-dimethylaminophenyl)squaraine from dialkyl squarates. Mechanism and scope of the synthesis

Abstract: The mechanism and the scope of the synthesis of bis(4-dialky1aminoaryl)squaraines from di-n-butyl squarate and N,N-dialkylanilines have been studied. Results show that water and acid are key factors of the synthesis, and these two factors have been optimized. Yields of squaraine are also found to be sensitive to the steric effect provided by the alkyl chain in dialkyl squarates as well as to the concentration of the aniline reagent used in the synthesis. Mechanistic results suggest that alkyl squarate is the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…147 Law and Bailey reported that squaraines could also be synthesized from dialkyl squarate and iV^V-dimethylaniline derivatives (ester route, Scheme II). 154 Although the synthetic efficiency and scope of this new route are similar to the acid route, xerographic measurements showed that squaraines synthesized by this procedure consistently exhibit better xerographic properties, namely lower dark decay and higher charge acceptances.155 It was concluded from a mechanistic study that, due to the change in reaction condition, the microcrystalline squaraine products from the ester route are smaller in particle size and have a different crystallographic orientation. This morphological change results in "purer" squaraine samples and improvements in xerographic properties.…”
Section: B Squaralnesmentioning
confidence: 99%
“…147 Law and Bailey reported that squaraines could also be synthesized from dialkyl squarate and iV^V-dimethylaniline derivatives (ester route, Scheme II). 154 Although the synthetic efficiency and scope of this new route are similar to the acid route, xerographic measurements showed that squaraines synthesized by this procedure consistently exhibit better xerographic properties, namely lower dark decay and higher charge acceptances.155 It was concluded from a mechanistic study that, due to the change in reaction condition, the microcrystalline squaraine products from the ester route are smaller in particle size and have a different crystallographic orientation. This morphological change results in "purer" squaraine samples and improvements in xerographic properties.…”
Section: B Squaralnesmentioning
confidence: 99%
“…3,4-Dihydroxycyclobut-3-ene-1,2-dione, commonly known as squaric acid, condenses with two molar equivalents of an electron rich aromatic compound, such as an aniline or phenol, 1 to form intensely coloured squaraine dyes. Bis(anilino)squaraines and bis(benzothiazolium)squaraines, in particular, have been studied for a whole range of photophysical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Butylsquarate (3-butoxy-4-hydroxy-1,2-dioxocyclobut-3-ene) was proposed as the reactive intermediate [28,29], firstly reacting with one molecule of the (hetero)aromatic compound to give an intermediate semisquaraine that subsequently undergoes a second condensation with another molecule of the same (hetero)aromatic compound to yield the final squaraine dye. The success of the reaction depends primarily on the nucleophilicity of the (hetero)aromatic species [30,31].…”
Section: Methodsmentioning
confidence: 99%